Digestion of Fiber and Increased Crude Protein in Corn Cob - J. F. Al-maadhidi; M. T. Al-khatib (Journal of Madenat Alelem University College, 2010)
Corn cob is agricultural by products rich in cellulosic fibers and poor in proteincontents (1), therefore to make it available for feeding of ruminants, fishes andpoultry need processing to decrease the fibers and increasing the protein contents.Chemical digestion and aerate fermentation had been conducted. Crushed, milledcorn cob (0.1 – 0.5 cm) was socked in 1 03 rof devalcotua dna noitulos HOaN ٪minutes at 121Cº and1.5 Lb/cm 3 . After cooling, fermentation experiment of 10 %suspended corn cob in distilled water was adjusted to pH 5 and 4 L/g1 ,sessalom ٪urea were added, inoculated with 50ml/L yeast culture as initial were conducted inK ell fermentor of 20L working capacity under controlled conditions (30 Cº, 150 rpm,pH 5 and aeration 2m 3 /h), experiments duration were 72hrs. Fermentor contentswere dried in electric oven at 70 Cº. Dried material was homogenized and analyzedfor protein content using microkeldal method and for fiber determination usingInfra analyzer instruments. Results from digestion and fermentation experimentsrevealed significant decrease in fiber contents, it was decreased from 41.7 ni ٪untreated control to 7.58 ± 1.7 ni ٪4.2 morf desaercni saw nietorp eht elihw ,٪nonfermented control to 16.3- elbat( tnemirepxe noitatnemref fo tcudorp ni 75.2±٪1). These results indicate a highly improved in feeding quality of corn cob, which canbe used successfully for ruminant, fishes and poultry feeding.